2022
DOI: 10.48550/arxiv.2204.11333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the size of good-for-games Rabin automata and its link with the memory in Muller games

Abstract: In this paper, we look at good-for-games Rabin automata that recognise a Muller language (a language that is entirely characterised by the set of letters that appear infinitely often in each word). We establish that minimal such automata are exactly of the same size as the minimal memory required for winning Muller games that have this language as their winning condition. We show how to effectively construct such minimal automata. Finally, we establish that these automata can be exponentially more succinct tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a follow-up work, Casares, Cocombet and Lehtinen [6] achieve a larger gap between GenMem(W ) and ChrMem(W ). Namely, they construct a Muller W over n colors such that GenMem(W ) is linear in n and ChrMem(W ) is exponential in n.…”
Section: Have the Same Sets Of Colors Occurring Infinitely Often In Themmentioning
confidence: 90%
See 2 more Smart Citations
“…In a follow-up work, Casares, Cocombet and Lehtinen [6] achieve a larger gap between GenMem(W ) and ChrMem(W ). Namely, they construct a Muller W over n colors such that GenMem(W ) is linear in n and ChrMem(W ) is exponential in n.…”
Section: Have the Same Sets Of Colors Occurring Infinitely Often In Themmentioning
confidence: 90%
“…First, Casares [5] showed that ChrMem(W ) equals the minimal size of a deterministic Rabin automaton, recognizing W , for every Muller W . Second, Casares, Colcombet and Lehtinen [6] showed that GenMem(W ) equals the minimal size of a goodfor-games Rabin automaton, recognizing W , for every Muller W . The latter result complements an earlier work by Dziembowski, Jurdzinski and Walukiewicz [9], who characterized GenMem(W ) for Muller W in terms of their Zielonka's trees [14].…”
Section: Have the Same Sets Of Colors Occurring Infinitely Often In Themmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory requirements have been precisely characterized for some classes of ω-regular objectives (not encompassing the class of DBA-recognizable objectives), such as Muller conditions [27,62,17,18] and safety specifications, i.e., objectives that are closed for the Cantor topology [25]. The latter also uses the order of the equivalence classes of the right congruence as part of its characterization.…”
Section: Contributionsmentioning
confidence: 99%